METHODS OF DEVELOPING INDEPENDENT THINKING OF STUDENTS IN RUSSIAN LANGUAGE LESSONS (E Global Congress, 2025)
The article discusses methods of developing independent thinking of students in Russian language lessons. The main attention is paid to active teaching methods, such as group discussions, debates, posing target questions, problem tasks, which contribute to the development of critical and analytical thinking. The article describes methods aimed at developing students' independence in finding solutions, argumentation and analyzing information. Recommendations for the effective use of these methods in the educational process are also offered.